Protestantismo brasileiro : a árvore, a teologia e o mosaico - Maciel, Moisés Brasil (2016)
This dissertation contemplates three aspects of Brazilian Protestantism: Genealogic Tree, Theology and the Mosaic. In Genealogy Tree, the work starts the period before the Reform, follows the Reform, comes to American continent through the colonization of the United States to officially reach Brazil in 1822. Soon after, by the way of missions and immigrations, it walks up to the current days with the appearance of the main Protestant denominations in Brazil. In Theology, the most important theologycal systems in Brazil are studied, specially the ones which systematicaly keep their theology and neopetencostalism which begins to draw his own theology. The dissertation concludes with the Mosaic of Brazilian Protestantism establishing some common points in various denominations, even with the passage of time, still retains traces of the Protestant Reform.